A nucleation--elongation mechanism for the self-assembly of side polar sheets of smooth muscle myosin. - Cross, R A (1991)
Self-assembled filaments of smooth muscle myosin were observed by low dose electron microscopy to be flat side-polar sheets, in which the component molecules appeared straight and close-packed. Fraying experiments released small oligomers, in which molecules were staggered in parallel by about +/- 14 nm relative to two immediate neighbours, and were bound also to an antiparallel partner via a approximately 14 nm overlap at the very tip of the tail. We suggest a filament model which preserves these packing relationships. Adding stoichiometric amounts of MgATP to the filaments caused them to disassemble completely by progressive loss of material from their ends, at a limiting rate equivalent to about 2 monomers per second per end in physiological saline. The rate of the competing association reaction varied linearly with the monomer concentration, as determined in pressure-jump experiments. This suggests that myosin monomers, rather than dimers or higher oligomers, are the building blocks of these filaments. Shearing and annealing of assembled filaments appeared negligible on a time scale of a few hours. In consequence, filament number and filament length were dependent on the rate at which monomers were supplied to the assembly reaction, and on the number of filaments already present at the start of the assembly reaction.